Secure Digital Transactions in The Education Sector Using Blockchain - Nouman, Muhammad; Ullah, Kareem; Azam, Muhammad (EAI Endorsed Transactions on Scalable Information Systems, 2021)
A blockchain is a decentralized, distributed peer-to-peer network that allows one node to communicate with other nodes. When using blockchain technology in education, data or records can be stored permanently without fear of hacking du e to the secure hashing algorithms in blockchain technology. The goal is to create a new blockchain technology that has the potential to form a decentralized application in education, with the help of different components, such as Meta Mask, IPFS, Ganache, and other test networks such as Rinke by and Rostand, as well as Web3 JS and Ethereum cryptocurrency. This research was applied in the following ways: (a) analysing the three most well-known blockchain cryptocurrencies (Bitcoin, Litecoin, and Ethereum); (b) investigating the features and issues surrounding the Bitcoin cryptocurrency, and (c) creating a graphical interface for the IPFS bandwidth analysis for storing files on the network using Web3 JS and Smart Contracts. As a result, this research paper provides a proper demonstration of data storage without the use of a centralized system (decentralized and distributed P2P network) using IPFS to aid in data segmentation for storage purposes.